Correlation of serum B lymphocyte stimulator and β2 microglobulin with autoantibody secretion and systemic involvement in primary Sjögren's syndrome. Issue 7 (7th January 2005) - Gottenberg, J-E; Busson, M; Cohen-Solal, J; Lavie, F; Abbed, K; Kimberly, R P; Sibilia, J; Mariette, X
Abstract : Background: In primary Sjögren's syndrome (pSS), extraglandular involvement might result from more intense stimulation of autoreactive B cells. Thus markers of B cell activation could be useful in the clinical assessment of this disease. Objective: To investigate the association of serum B lymphocyte stimulator (BLyS) and β2 microglobulin with autoantibody production and extraglandular involvement in pSS. Methods: Serum concentrations of BLyS and β2 microglobulin were analysed in 177 patients with pSS according to the American–European consensus group criteria. Serum β2 microglobulin was determined serially in 25 patients. Results: Autoantibody secretion (presence of anti-SSA antibody alone or of both anti-SSA and anti-SSB) was associated with increased serum BLyS and β2 microglobulin. No correlation was found between BLyS and β2 microglobulin levels (p = 0.36). Serum concentrations of β2 microglobulin and C reactive protein and positive anti-SSB antibody results were associated with extraglandular involvement on univariate analysis (p<10 −4, p = 0.003, and p = 0.004, respectively). Serum β2 microglobulin was also significantly increased in patients with extraglandular involvement without autoantibodies (mean (SD): 1.75 (0.7) v 1.39 (0.5) mg/l, p = 0.039). Multivariate analysis showed that extraglandular involvement was associated only with increased serum β2 microglobulin (p = 0.035, odds ratio = 2.78 (95% confidence interval, 1.07 to 7.22)). Among the 25 patients who had serial determinations of serum β2 microglobulin, the concentrations were increased in all those with disease flare and decreased in three following treatment. Serum BLyS, gamma globulin, IgG, and rheumatoid factor levels were not associated with features of systemic involvement. Conclusions: Serum β2 microglobulin and BLyS reflect B cell activation in different ways in pSS. Serum β2 microglobulin assessment could be helpful as an activity marker in pSS.